UMP distributes korban meat for 109 recipients to observe Aidiladha - Nor Salwana, Mohammad Idris (2021)
PEKAN, 22 July 2021 - The Islamic and Human Development Centre (PIMPIN) of Universiti Malaysia Pahang (UMP) recently organised the Ibadah Korban and Akikah programme by sacrificing five cows in UMP Pekan to enliven the Aidiladha atmosphere.